(untitled) (Research, Society and Development, 2020)
University Hospitals have a strategic role in the perspective of improving comprehensive care. In this sense, the study was guided by the research question: what is the role of University Hospitals in assisting the parturient and newborn in Brazil? The objective being to know the practice of teaching, research and assistance in childbirth and birth developed in university hospitals. Method: integrative literature review, carried out on the virtual platforms Medline, Lilacs, BDenf and Scielo studies from Brazil published from 2012 to 2020, in Portuguese and English. Results: after analysis, it was possible to divide the answer to the research question into three thematic categories: a) university hospitals - locus of specialized comprehensive assistance; b) university hospitals: teaching locus - research in the pregnancy-puerperal scenario and c) university hospitals: teaching locus - research in the neonatal scenario. Conclusion: Although the study has limitations, in view of the vast amount of activities developed in hospital environments, hospitals have tactical performance in terms of improving care practices and advances in teaching and research, being environments for both the creation of new scientific knowledge and for the application of technological innovations